Minangkabau’s Doro Tradition: Coexistence of Customary Law and Islamic Law in Caning Punishment - Ismail, Ismail; Hendri, Novi; Nurhakim, Putri Rahmah (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2023)
The present study intends to investigate the coexistence of customary law and Islamic law in doro tradition of Minangkabau Tribe. It poses three research questions as follows: (1) How is the philosophy of “Adat Basandi Syarak, Syarak Basandi Kitabullah” manifested in the doro tradition?; (2) In which ways do the customary law and Islamic law coexist in the doro tradition?; (3) How are the implications of doro tradition in the prevention of adultery vis-à-vis the principles of justice and human rights? The research used a qualitative design and gathered the data through observation and in-depth interviews. The findings show that the doro tradition refers to, and thus, accentuates the Minangkabau philosophy of “Adat Basandi Syarak, Syarak Basandi Kitabullah, Syarak Mangato Adat Mamakai”. The coexistence of customary law and Islamic law in the tradition occurs is emphasized in the implementation of caning and cumulative fines. The doro tradition is regarded as very effective as a punishment for adultery cases, as it also does not conflict with the principles of justice and human rights.